Mass loss of four commercially available heat-polymerized acrylic resins after toothbrushing with three different dentifrices - Karina M. Freitas-Pontes; Cláudia H. Silva-Lovato; Helena F. O. Paranhos (University of São Paulo, 2009)
The association between a toothbrush and a dentifrice is the most used denture cleaning method. The purpose of this study was to evaluate the abrasiveness of specific and non-specific denture cleaning dentifrices on different heat-polymerized acrylic resins. Sixteen specimens (90x30x3mm) of each acrylic resin (QC-20, Lucitone 550, Clássico, Vipi-Cril) were prepared and randomly assigned to 4 groups: 1: control (distilled water), 2: Colgate, 3: Bonyplus and 4: Dentu-Creme. The specimens were subjected to simulated toothbrushing in an automatic brushing machine using 35,600 brush strokes for each specimen. Brushing abrasion run at a 200-g load with the specimens immersed in 2:1 dentifrice/water slurry. Specimens were reconditioned to constant mass and the mass loss (mg) was evaluated. Data were analyzed by 2-way ANOVA and Tukey's test (a=0.05). Analysis of dentifrices' abrasive particles was made by scanning electron microscopy. Colgate produced the greatest mass reduction (42.44 mg, p<0.05), followed by Dentu-Creme (33.60 mg). Bonyplus was the less abrasive (19.91 mg), similar to the control group (19.69 mg) (p>0.05). The mass loss values indicated that QC-20 (33.13 mg) and Lucitone 550 (33.05 mg) resins were less (p<0.05) resistant to abrasion than Clássico (26.04 mg) and Vipi-Cril (23.43 mg). In conclusion, Colgate produced the greatest abrasion. Specific dentifrices for dentures tend to cause less damage to acrylic resins.